Mapping the evolution of the central government apparatus in China. (March 2020) - Ma, Liang; Christensen, Tom
The structure of political and administrative institutions is important for achieving public goals. It is not fixed, however, but may change as a result of environmental and cultural processes or because of changes in leadership. Structural changes in the central government apparatus feature prominently in the recent strand of reform and change literature, but we know little about structural changes in contexts other than Western democracies. In this article, we analyze the main types of and possible reasons for structural changes in the central government apparatus in China over the past 70 years. We find interesting patterns of structural change in line with administrative developments. Using the multiple perspectives of organization theory, these can be primarily explained by political cycles or action taken by the central leadership, but they have also been influenced by cultural elements, economic growth, and societal transformation. Points for practitioners: We document the key patterns of organizational restructuring in China's central government from 1949 to 2016. Political cycles and economic reform and development are found to be the key drivers of structural evolution. The results show that the political will of top leaders plays a crucial role in navigating structural reforms, yet institutional reforms are still largely confined to rhetoric and symbolism without substantively transforming the landscape of government architecture. Sustained structural reforms are difficult to achieve successfully, which suggests that alternative avenues may be required to streamline administrative processes and improve interagency coordination.